Health Belief Model (HBM) Approach in Sexually Transmitted Infection Prevention Efforts in Men Who Have Sex with Men (LSL) Communities - Multy Syaddam Nirwan; Arina Rizki Fauziah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Sexually Transmitted Infections (STIs) among LSL are caused by sexual behavior driven by sexual desire, either with the opposite sex or the same sex. The forms of this behavior can vary, from feelings of attraction to dating, making out, and intercourse. Sexual behavior carried out by men is much more complex, where it can be seen that men who have sex with men can have sex with women and transvestites. Geographically, the location of Palu City is very strategic, potentially receiving imports of HIV/AIDS and STI transmission. This is because the smooth mobility of the population between provinces is quite high, because there are seaports, airports that can connect with other areas, besides that land routes are also smooth. The purpose of this study was to obtain information, examine and analyze the Health Belief Model (HBM) approach in efforts to prevent Sexually Transmitted Infections in the Men Who Have Sex with Men (MSM) Community in Palu City. This study uses qualitative research using a phenomenological approach to explore the phenomenon of STI prevention efforts with the Health Belief Model (HBM) approach in Palu City and Focus Group Discussion. The main informants in this study were MSM in Palu City. Supporting informants were consumers/friends of MSM who were directly involved in social interactions with those studied, and the key informants in this study were managers of the HIV/AIDS and STI disease program in Palu City who knew and had various information related to the world of LSL.